2002
DOI: 10.1128/jvi.76.13.6502-6509.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Genome Segment 7 (NSP3) Is a Determinant of Extraintestinal Spread in the Neonatal Mouse

Abstract: We used the neonatal mouse model of rotavirus infection to study extraintestinal spread following oral inoculation. Five-day-old pups were inoculated with either SA11-Cl3, SA11-Cl4, SA11-4F, RRV, or B223. By using virus detection in the liver as a proxy determination for extraintestinal spread, rotavirus strains capable of extraintestinal spread at high frequency (rhesus rotavirus [RRV]) and very low frequency (SA11-Cl4) were identified. Both strains productively infected the gastrointestinal tract. Oral inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 35 publications
(31 reference statements)
5
54
2
1
Order By: Relevance
“…Single-gene reassortants (i.e., all but one gene derived from one parent) allow for the determination of the function of that gene. Using such techniques, the extraintestinal spread of rotavirus has been linked to the NSP3 gene derived from RRV (23). The results of the current studies provide the framework for further manipulation.…”
Section: Vol 81 2007mentioning
confidence: 99%
See 2 more Smart Citations
“…Single-gene reassortants (i.e., all but one gene derived from one parent) allow for the determination of the function of that gene. Using such techniques, the extraintestinal spread of rotavirus has been linked to the NSP3 gene derived from RRV (23). The results of the current studies provide the framework for further manipulation.…”
Section: Vol 81 2007mentioning
confidence: 99%
“…Inoculation with the mouse strain EDIM and the human strain Wa caused no clinical signs of hepatobiliary injury, and consistent with the lack of injury, we found no detectable infectious virus within the liver. Previous studies have shown that the extraintestinal spread of rotavirus is strain dependent (22,23,32). In those studies, the presence of virus within the liver was used as a marker of spread (22,23).…”
Section: Vol 81 2007mentioning
confidence: 99%
See 1 more Smart Citation
“…While the extraintestinal spread of rotavirus in the neonatal mouse model is well documented, the determinants and mechanisms of the spread of the virus are not as clear. It is known that extraintestinal spread occurs in a rotavirus straindependent manner (16,29). We previously demonstrated that among SA11-clone 4 (SA11-Cl4) and Rhesus rotavirus (RRV) reassortants, spread of the virus to the liver was significantly associated with RRV-derived genome segment 7, which encodes NSP3 (16).…”
mentioning
confidence: 99%
“…Animal studies support these observations. Rotavirus and/or rotavirus antigen was recovered from the blood, liver, spleen, kidneys, lungs, and mesenteric lymph nodes (MLN) of orally inoculated mice (1,2,4,10,16,27), and mouse models for rotavirusinduced hepatitis (29) and biliary atresia (25) were previously described.…”
mentioning
confidence: 99%